2016
DOI: 10.1038/srep31790
|View full text |Cite
|
Sign up to set email alerts
|

Infection-induced behavioural changes reduce connectivity and the potential for disease spread in wild mice contact networks

Abstract: Infection may modify the behaviour of the host and of its conspecifics in a group, potentially altering social connectivity. Because many infectious diseases are transmitted through social contact, social connectivity changes can impact transmission dynamics. Previous approaches to understanding disease transmission dynamics in wild populations were limited in their ability to disentangle different factors that determine the outcome of disease outbreaks. Here we ask how social connectivity is affected by infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
185
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(191 citation statements)
references
References 46 publications
6
185
0
Order By: Relevance
“…Second, we assume that social contacts do not covary with pathogen characteristics and remain unaltered after an infection is introduced into a population. Infection has in fact been shown to alter the social connectivity of hosts (Croft et al., ; Lopes, Block, & König, ) and recent theoretical work has demonstrated that negative correlations between transmissibility and contact rate can diminish the impact of connectivity (White, Forester, & Craft, 2017). Future species‐specific studies can take advantage of host‐specific experimental manipulations, where possible, to gain in‐depth insight towards host behaviour—infection feedback (Ezenwa, Ghai, McKay, & Williams, ; Silk, Croft, Delahay, Hodgson, Boots, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we assume that social contacts do not covary with pathogen characteristics and remain unaltered after an infection is introduced into a population. Infection has in fact been shown to alter the social connectivity of hosts (Croft et al., ; Lopes, Block, & König, ) and recent theoretical work has demonstrated that negative correlations between transmissibility and contact rate can diminish the impact of connectivity (White, Forester, & Craft, 2017). Future species‐specific studies can take advantage of host‐specific experimental manipulations, where possible, to gain in‐depth insight towards host behaviour—infection feedback (Ezenwa, Ghai, McKay, & Williams, ; Silk, Croft, Delahay, Hodgson, Boots, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent across the two different formulations of final transmission probability that were simulated. While intuitive, these results are important because reduction of activity and contact rate because of infection are welldocumented (Croft et al 2011, Welicky and Sikkel 2015, Lopes et al 2016), but less commonly incorporated into disease models.…”
Section: Discussionmentioning
confidence: 99%
“…In natural systems, it has been demonstrated that these interrelated facets of transmission can vary widely between individuals. In fact, empirical studies suggest that unequal contact rates are the rule rather than the exception (Craft and Caillaud 2011), that contact rates can vary with infection-induced behavioral changes (Croft et al 2011), and that these changes are likely non-uniform across individuals (Lopes et al 2016). Innate and plastic heterogeneity in susceptibility to infection has been documented for several species (Dwyer et al 1997, Beldomenico and Begon 2010, Gibson et al 2016, and variability in infectiousness has also been observed, particularly when concomitant infections are present (Cattadori et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…). Furthermore, these changes in behaviour have been shown to alter contact network structure, with implications for transmission (Tunc & Shaw ; Lopes, Block & König ). Therefore, accounting for the co‐dynamics of network structure and infection is key to improving our understanding of disease spread and control in many systems (fig.…”
Section: Introductionmentioning
confidence: 99%
“…; Tunc & Shaw ); however, there has been relatively little use of empirical data to explore this topic (but see Rohani, Zhong & King ; Reynolds et al . ; Lopes, Block & König ). Using empirical data to test hypotheses about the relationship between sociality and disease (e.g.…”
Section: Introductionmentioning
confidence: 99%